A quantitative study of test anxiety and its influencing factors among medical and dental students - Nazir, Muhammad A. (J Taibah Univ Med Sci, 2021)
OBJECTIVE: The study was conducted to assess test anxiety and its influencing factors on medical and dental students. METHODS: A cross-sectional study was conducted among students from three private and public medical and dental colleges in the Punjab province of Pakistan. The survey included statements about the demographic profile of the study participants and used the Test Anxiety Inventory (TAI) by Spielberger. RESULTS: The study included 680 students with a mean age of 20.93 ± 1.76 years. About half the sample (51.8%) scored high on test anxiety (TAI score > 45), and the mean TAI score was slightly higher for the dental (47.75 ± 11.45) than medical students (46.42 ± 12.79). Female students had a significantly higher mean TAI score (48.45 ± 12.79) than male students (41.85 ± 8.91; p < 0.001). The students from private colleges had a significantly greater test anxiety score (50.15 ± 13.23) than students from public colleges (42.88 ± 9.7; p < 0.001). Students whose parents were graduates from a college or university perceived significantly increased test anxiety than those of parents with no/school education (p < 0.001). A female gender (adjusted odds ratio (AOR) 2.10, 95% CI:1.37, 3.22), being a private college student (AOR 2.88, 95% CI:1.90, 4.38), and having a mother with a college or university education (AOR 2.05, 95% CI: 1.25, 3.35) were significantly associated with high on test anxiety. CONCLUSION: In our study cohort, test anxiety was common among medical and dental students. A female gender, being a student from a private college, and having a mother with a high education were significantly associated with high test anxiety. The study findings may guide the development of programs that can reduce students’ test anxiety and potentially improve their education.